Consumer Behavior of Potato Donuts in Malang, Indonesia: An Extended Theory of Planned Behavior (ETPB) Approach - Isma Munawaroh; Abdul Wahib Muhaimin; Riyanti Isaskar (Universitas Muhammadiyah Malang, 2024)
The potato donut industry has experienced a decline in revenue, compounded by consumer complaints regarding service quality post-COVID-19. Understanding consumer behavior and seller service standards is crucial for enhancing purchasing decisions. This study aims to investigate the influence of attitude towards behavior, subjective norms, perceived behavioral control, and service quality on purchase intention for potato donuts, as well as the impact of service quality and behavioral control on purchase decisions, and the pivotal role of purchase intention therein. A sample of 70 respondents aged 15-55 participated, with primary data collection conducted via online questionnaires distributed through Google Forms in November 2023. Structural equation modeling (SEM) analysis performed using WarpPLS 8.0 software revealed that attitudes towards behavior, subjective norms, and perceived behavioral control positively and significantly influenced purchase intention for potato donuts, while service quality yielded no significant effect. Neither perceived behavioral control nor service quality exerted influence on purchase decisions for potato donuts. Notably, purchase intention emerged as a highly significant determinant of purchase decisions.